Baseline cardiac function checkup in patients with gastric or breast cancer receiving trastuzumab or anthracyclines - Taisuke Ishii; Tomone Watanabe; Takahiro Higashi (Cancer Medicine, 2023)
Abstract Background Although trastuzumab and anthracyclines are frequently used to treat breast cancer (BC) and gastric cancer (GC), cardiotoxicity is a serious concern. The cardiac function assessment is recommended at baseline before initiating treatment. However, the prevalence rates of baseline cardiac checkups are unknown. Methods The national database of hospital‐based cancer registries linked to the health services‐utilization data was used to study patients with newly diagnosed stage IV BC and GC (n = 6271) who received trastuzumab (n = 4324, 69.0%) or anthracyclines between January 2012 and December 2015. The baseline ultrasound echocardiogram (UCG) performance rate and factors related to adequate UCG performance for all patients and those receiving trastuzumab were analyzed. Results The adequate baseline UCG checkup rate was higher in patients treated with trastuzumab than in those treated with anthracyclines (71.8% vs 44.1%, respectively). Additionally, patients with GC were less likely to receive an adequate baseline UCG performance than those with BC (70.4% vs 75.0%, respectively). After adjusting for potential confounders, patients with anthracycline‐treated BC and GC were less likely to receive adequate baseline UCG performance than those with trastuzumab‐treated BC (odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.20–0.28, and OR: 0.07, 95% CI: 0.03–0.16, respectively). Furthermore, patients with trastuzumab‐treated GC were less likely to receive adequate baseline UCG performance than those with BC (OR: 0.65, 95% CI: 0.50–0.84). Conclusions The baseline UCG was less likely to be performed in patients receiving anthracyclines than in those receiving trastuzumab, as well as in patients with GC than in those with BC.